Continuation Versus Discontinuation of Sodium‐Glucose Cotransporter‐2 Inhibitors and Cardiorenal Outcomes Among Patients With Type 2 Diabetes and Chronic Kidney Disease: A Nationwide Cohort Study With a Target Trial Emulation Framework - Yaa‐Hui Dong; Chia‐Hsuin Chang; Li‐Chiu Wu; Sengwee Toh (Clinical and Translational Science)
ABSTRACT Clinical guidelines recommend continuation of sodium‐glucose cotransporter‐2 inhibitor (SGLT2i) treatment when renal function deteriorates among patients with type 2 diabetes. However, the recommendation is not currently supported by research specifically designed to compare continuation versus discontinuation of SGLT2is for patients who have received the treatment for a while before experiencing renal function deterioration. Using linked Taiwanese databases with claims and clinical data and a target trial emulation framework, we conducted a nationwide cohort study to investigate the association between SGLT2i continuation and major cardiorenal outcomes after renal function declined. We identified patients with type 2 diabetes who received SGLT2is during 2016–2020, who either continued or discontinued SGLT2is within 180 days after their eGFR declined below 45 mL/min/1.73 m2. The study outcomes were myocardial infarction, stroke, heart failure, acute kidney injury, and all‐cause mortality. We estimated the on‐treatment and intention‐to‐treat hazard ratios (HRs) and 95% confidence intervals (CIs) comparing SGLT2i continuation versus SGLT2i discontinuation, adjusting for baseline and time‐varying covariates using inverse probability weighting. Among 11,467 eligible patients, the on‐treatment HR associated with SGLT2i continuation was 0.83 (95% CI, 0.59–1.18) for myocardial infarction, 0.74 (0.56–0.95) for stroke, 0.58 (0.49–0.69) for heart failure, 0.53 (0.45–0.63) for acute kidney injury, and 0.51 (0.42–0.61) for all‐cause mortality. The results did not change meaningfully in the intention‐to‐treat analysis or within pre‐specified patient subgroups, including patients with eGFR below 30 mL/min/1.73 m2 or prior acute kidney injury. Our findings provide scientific evidence to support continuing SGLT2i use when renal function declines during the SGLT2i treatment course.